2011
DOI: 10.1074/jbc.m111.224493
|View full text |Cite
|
Sign up to set email alerts
|

Association of Botulinum Neurotoxin Serotype A Light Chain with Plasma Membrane-bound SNAP-25

Abstract: The botulinum neurotoxins (BoNTs) 3 are the most toxic proteins for humans (1, 2). The potency and longevity of BoNT intoxication have facilitated use of BoNTs as therapeutic agents (3-5) and as potential biological weapons (6, 7). There are seven BoNT serotypes (A-G), which are organized as dichain proteins, where the N-terminal catalytic light chain (LC) and C-terminal heavy chain are linked by a disulfide bond (8). Neurotrophic activity is based upon two properties of the BoNTs, binding to a neuron-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 39 publications
1
50
1
Order By: Relevance
“…The results indicate that association of GFP-LCA with SNARE proteins is weak and/or transient and, hence, is unlikely to be responsible for membrane tethering of LCA as was previously suggested (Chen and Barbieri, 2011). The data provide no evidence for a specific interaction between LCA and adaptor proteins complexes.…”
Section: Identification Of Proteins That Interact With Lca Through Thcontrasting
confidence: 34%
See 1 more Smart Citation
“…The results indicate that association of GFP-LCA with SNARE proteins is weak and/or transient and, hence, is unlikely to be responsible for membrane tethering of LCA as was previously suggested (Chen and Barbieri, 2011). The data provide no evidence for a specific interaction between LCA and adaptor proteins complexes.…”
Section: Identification Of Proteins That Interact With Lca Through Thcontrasting
confidence: 34%
“…Membrane cytoskeleton proteins rather than SNARE proteins are preferred LCA-interacting partners Recent studies have suggested that the interaction of LCA and SNAP-25 is responsible for stable association of LCA with the plasma membrane in neurons (Chen and Barbieri, 2011). However, our results from a global analysis of the LCA interactome in SiMa cells (Table 1; supplementary material Table S1) indicate that association of GFP-LCA with SNAP-25 is weak and transient and hence is unlikely to be responsible for the stabilization of LCA.…”
Section: Discussion New Properties Of Lca Dileucine Motifmentioning
confidence: 99%
“…Neurons-BoNT/A promotes paralysis through the cleavage of 9 amino acid residues from the C terminus of SNAP25 (21,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). We next investigated whether Dyngo-4a could prevent the cleavage of SNAP25 in hippocampal neurons.…”
Section: Dyngo-4a Prevents Bont/a-induced Snap25 Cleavage In Culturedmentioning
confidence: 99%
“…Within the periphery of the motor neuron, the LC cleaves SNARE proteins, resulting in loss of stimulatory signaling between neurons and muscles, yielding flaccid paralysis. The LC of BoNT/A localizes to the plasma membrane to target synaptosomal-associated protein 25 (SNAP25) for cleavage within neurons (6).…”
mentioning
confidence: 99%